2012
DOI: 10.1094/cm-2012-1211-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Pyroxsulam and Chlorpyrifos Applied the Same Day Injures Wheat

Abstract: Field experiments were conducted in northwestern Kansas for two years to determine the effect of chlorpyrifos application timing on winter wheat response to pyroxsulam applied postemergence. Pyroxsulam at 18.4 g ai/ha was applied in spring when wheat was 10 to 15 cm tall. Chlorpyrifos at 260 g ai/ha was applied 3 or 7 days before, and 3 or 7 days after pyroxsulam application. Also a treatment of pyroxsulam and chlorpyrifos applied on the same day was included. When pyroxsulam and chlorpyrifos were applied on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The high injury observed with the combination pyroxsulam + chlorpyrifos is in accordance with other studies carried out under field conditions. Reddy et al (2010) also observed synergism in the combinations of these pesticides, reducing RT of wheat plants, but without compromising grain yield. Several factors may influence plant response to an herbicide or product combination, such as application stage, climate conditions, and even the differential tolerance presented by cultivars (Everitt and Keeling, 2009;Galon et al, 2010;Robinson et al, 2015).…”
mentioning
confidence: 83%
“…The high injury observed with the combination pyroxsulam + chlorpyrifos is in accordance with other studies carried out under field conditions. Reddy et al (2010) also observed synergism in the combinations of these pesticides, reducing RT of wheat plants, but without compromising grain yield. Several factors may influence plant response to an herbicide or product combination, such as application stage, climate conditions, and even the differential tolerance presented by cultivars (Everitt and Keeling, 2009;Galon et al, 2010;Robinson et al, 2015).…”
mentioning
confidence: 83%